Analysis of food and nutrition security, The covid 19, western region of Honduras (Nexo Revista Científica, 2022)
This document analyzes some of the main topics and challenges that influence the causes of food and nutritional insecurity at the community level of the western region of Honduras, in the departments of Copan, Lempira and Ocotepeque, framed in health and environmental emergencies. of COVID-19 and Hurricane ETA and IOTA in Honduras, through the use of an applied survey, with the purpose of evaluating the impact and determining the needs of the population in terms of poverty, hunger and other basic needs, that this research serve to guide the policies and strategies of food and nutrition security, the development objectives are emphasized in the reconstruction of a vision of the country, which strengthens the different pillars of SAN, in the same way to provide through the findings a document that serves to find a methodology that establishes an input with the purpose of generating knowledge and at the same time with the results create awareness of the efficient conditions for increasing the coverage of interventions induced to the integration of continuous improvement strategies with respect to region 03 of the western part of the country in terms of topics such as health, education, productivity, safety, food sovereignty and pillars of food safety.